How Does the Parent–Adolescent Relationship Affect Adolescent Internet Addiction? Parents’ Distinctive Influences - Qi, Huaiyuan; Kang, Qinhong; Bi, Cuihua (Frontiers in Psychology, 2022)
Although previous research has demonstrated that parent–adolescent relationships have a significant effect on adolescent Internet Addiction (IA), the mechanisms underlying these associations and parental differences in these effects have received insufficient attention. We investigated the mediating role of Perceived Social Support and Dual System of Self-Control (DSSC) in the relationship between Father-Adolescent Relationships/Mother-Adolescent Relationships (FAR/MAR) and adolescent IA, as well as the differences in the effects of FAR and MAR. A cross-sectional survey of 732 Chinese adolescents was conducted using the Adolescent Pathological Internet Use Scale, Parent–Adolescent Relationship Scale, Multidimensional Scale of Perceived Social Support, and Dual System of Self-Control Scale. Multiple linear regression analysis, Pearson correlation analysis and structural equation modeling were used. The results of structural modeling analysis showed that neither FAR nor MAR directly predicted adolescent IA. In contrast, FAR/MAR had an impact on adolescent IA mainly through the mediating effects of Perceived Social Support and Impulsive System. Furthermore, in the relationship between FAR/MAR and adolescent IA, the Impulsive System and Perceived Social Support both served as chain mediators, as did Perceived Social Support and the Reflective System. And more importantly, unlike FAR, MAR affects adolescent IA through the mediating effect of the Reflective System. Multiple linear regression showed that the regression coefficient of MAR on adolescent IA had stronger significance compared to FAR, MAR is deserving of more attention than FAR. These findings contribute to our understanding of the mechanisms underlying the association between FAR/MAR and adolescent IA and suggest that family relationship-focused training approaches are critical for suppressing adolescent IA. These interventions should be tailored to the unique circumstances of each family.